Legitimation Of National Health Services Law: The Right to Health for All Citizens - Risdawati, Irsyam; Zarzani, T. Riza (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Legal legitimacy of national health services is recognition or approval from the public for the laws governing national health services. This legal legitimacy is important to maintain the stability and continuity of national health services. The right to health is a human right recognized by various international legal instruments, including the Universal Declaration of Human Rights and the International Covenant on Economic, Social and Cultural Rights. The right to health is a fundamental right, because it is a prerequisite for the fulfillment of other human rights. The national health service law in Indonesia mandates that everyone has the right to health. However, in practice, there are still many people who cannot access quality and affordable health services. This is caused by various factors, including limited resources, lack of public awareness about the importance of health, and discrimination against vulnerable groups. Increasing the legal legitimacy of national health services can be done through various efforts, including: a) Disseminating information about the law: The government needs to socialize and educate the public about the laws governing national health services; b) Improving the quality of health services: The government needs to improve the quality of health services, both in terms of availability, affordability and quality; c) Increasing the accessibility of health services: The government needs to increase the accessibility of health services, so that people can easily access the health services they need; and d) Increasing the legal legitimacy of national health services is important for realizing the right to health for all citizens.